Answer:
Step-by-step explanation:
Given:
![(4x)^{(1)/(3)}\text{ - x = 0}](https://img.qammunity.org/2023/formulas/mathematics/high-school/za5s81e3l3k1rheev6iwdghqhkgu1b0wgf.png)
To find:
the steps in solving the expression and the value(s) of x
To determine the value of x, first, we will add x to both sides:
![\begin{gathered} (4x)^{(1)/(3)}\text{ -x + x = 0 + x} \\ (4x)\placeholder{⬚}^{(1)/(3)}\text{ }=\text{ x} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/twdlyb5j8ju87b0mcrh6nhs4ybmvlwkeal.png)
Next, cube both sides of the equation:
![\begin{gathered} ((4x)^{(1)/(3)})^3\text{ = x}^3 \\ ((4x)^{(3)/(3)})^\text{ = x}^3 \\ 4x\text{ = x}^3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/k25piso4pz0j7zrjuqw5kyj03hht6p7pkq.png)
Lastly, solve for x to determine the number of solutions:
![\begin{gathered} subtract\text{ 4x from both sides:} \\ x^3\text{ - 4x = 0} \\ x(x^2\text{ - 4\rparen = 0} \\ x\text{ = 0 or x}^2-4\text{ = 0} \\ \\ x^2\text{ - 4 = 0} \\ x^2\text{ = 4} \\ x\text{ = }\pm√(4) \\ x\text{ = }\pm2 \\ \\ The\text{ values of x = -2, 0, 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lfd9wp31bueca8k19w3wpp5gmaelfz9f6c.png)
![](https://img.qammunity.org/2023/formulas/biology/high-school/th3y35ipo1jqnb1pyz12bkyph7hz83zofb.png)
The first step in solving the equation is to add x to both sides. The second step is to cube both sides.
Solving this equation for x initially yields 3 possible solutions. Checking the solutions shows